2017
DOI: 10.1002/hed.24849
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of office examination with narrow band imaging for the diagnosis of head and neck squamous cell carcinoma and follow-up of premalignant lesions

Abstract: The NBI provided a greater accuracy than WLE and showed promising usefulness for the follow-up of premalignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 26 publications
1
27
0
Order By: Relevance
“…Many authors have also suggested a learning curve exists before reliable assessment can be made when using NBI 35,36 . Vilaseca and colleagues 37 suggested a learning curve of 200 examinations using NBI based on analysis of 480 patients. In this study, they analyzed 480 biopsy proven cancers in the head and neck region with WLE and NBI and subdivided the sample in groups of 100 patients according to the experience of the examiner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors have also suggested a learning curve exists before reliable assessment can be made when using NBI 35,36 . Vilaseca and colleagues 37 suggested a learning curve of 200 examinations using NBI based on analysis of 480 patients. In this study, they analyzed 480 biopsy proven cancers in the head and neck region with WLE and NBI and subdivided the sample in groups of 100 patients according to the experience of the examiner.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, they analyzed 480 biopsy proven cancers in the head and neck region with WLE and NBI and subdivided the sample in groups of 100 patients according to the experience of the examiner. They demonstrated that accuracy of detecting malignant lesions using NBI increases with experience and, plateaus after approximately 200 cases 37 …”
Section: Discussionmentioning
confidence: 99%
“…The present study was approved by the local ethics committee and was conducted in the ear, nose, and throat (ENT)‐endoscopy unit of a tertiary referral center. In that area, patients referred from other otolaryngologists with lesions suggestive of chronic laryngitis, oral ulcers, or suspected head and neck neoplasms are systematically examined under WLE and NBI, in accord with previous published protocol . Depending on the type of the lesion, the ENT examination and the finding on the NBI examination, either an office‐based biopsy or a surgical procedure under general anesthesia is performed.…”
Section: Methodsmentioning
confidence: 99%
“…In the presence of blood or thick mucus in the examined area, we tried to aspirate or asked the patient to drink some water. When the secretions could not be removed and the NBI pattern was not reliable, the patients were excluded from the study . Both WLE and NBI examinations were video recorded and afterward reviewed and classified by a senior staff member (I.V.).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation